2022
DOI: 10.1186/s40104-021-00656-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the proteomic profile of newly harvested corn and metagenomic analysis of the broiler intestinal microbiota

Abstract: Background The use of newly harvested corn in feed causes wet droppings in broilers and increased feed cost which was termed as “new season grain problem”. The present study was conducted to evaluate the proteomic profile of newly harvested corn and the subsequent influence on intestinal microbiol community for broiler chickens. Methods Newly harvested corn stored for either half a month (HM) or two months (TM) was used, and the pasting properties,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…The results of this study showed that broiler chickens fed newly harvested corn diets significantly decreased their digesta emptying time and increased visual fecal water content. Furthermore, during the test, the undigested feed was observed, which proved that there are indigestible components in newly harvested corn and feeding the newly harvested corn diet would cause diarrhea in broilers, this is consistent with the findings of Yin et al (2022) [ 1 ]. However, this phenomenon was alleviated by the supplementation of protease individually or in combination with glucoamylase in newly harvested corn diets.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study showed that broiler chickens fed newly harvested corn diets significantly decreased their digesta emptying time and increased visual fecal water content. Furthermore, during the test, the undigested feed was observed, which proved that there are indigestible components in newly harvested corn and feeding the newly harvested corn diet would cause diarrhea in broilers, this is consistent with the findings of Yin et al (2022) [ 1 ]. However, this phenomenon was alleviated by the supplementation of protease individually or in combination with glucoamylase in newly harvested corn diets.…”
Section: Discussionsupporting
confidence: 88%
“…Newly harvested corn contains a variety of ANFs, such as phytic acid, NSP, and soybean antigenic protein, which may reduce the bioavailability of nutrients [ 26 ] and increase viscoelastic properties of corn and the relative digesta viscosity [ 1 ], resulting in intestinal disorders, which, in turn, may lead to the occurrence of diarrhea in poultry. In addition, corn contains approximately 0.56–1.87 mg/g (DM) [ 4 ] native trypsin inhibitors, which may limit the contact of digestive enzymes with substrates in the intestinal tract of broilers [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively complex gut microecosystem plays an indispensable role in maintaining intestinal health, and the diversifications in microbiota are inseparable from dietary factors [1]. The common nonstarch polysaccharides (NSPs) in the diet, especially grain-derived arabinoxylan (AX), are inclined to increase the viscosity of chyme in the intestinal lumen and disturb the normal microflora [2].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of specific arabinoxylan-degrading enzymes on growth performance of broiler chickens 11 Values are given as the means based on six birds for each treatment (n = 6). The abbreviations of the groups are consistent with those in Table2BWG Body weight gain, g; FI Feed intake, g; F/G Feed-to-gain ratio, g/g; EPI European comprehensive production index; MRT Mortality, %; SEM Standard error of the mean a,b Means in a column with superscripts without a common letter differ (P < 0.05)…”
mentioning
confidence: 99%